2018
DOI: 10.1002/adma.201707522
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Iridium Incorporated in Cobalt Hydroxide for Efficient Oxygen Evolution Catalysis in Neutral Electrolyte

Abstract: Developing highly efficient catalysts for oxygen evolution reaction (OER) in neutral media is extremely crucial for microbial electrolysis cells and electrochemical CO reduction. Herein, a facile one-step approach is developed to synthesize a new type of well-dispersed iridium (Ir) incorporated cobalt-based hydroxide nanosheets (nominated as CoIr) for OER. The Ir species as clusters and single atoms are incorporated into the defect-rich hydroxide nanosheets through the formation of rich Co-Ir species, as revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
226
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(235 citation statements)
references
References 50 publications
8
226
1
Order By: Relevance
“…The 400‐SWNT/Pt exhibited a low overpotential of 27 mV to achieve current densities of 10 mA cm −2 , which are similar to those of Pt/C. Other precious metal‐based catalysts have also been reported, Zhang et al developed a well‐dispersed atomic Ir incorporated Co‐based hydroxide nanosheets with 9.7 wt% Ir. This catalyst displayed highly efficient OER catalytic performance with overpotential 373 mV at the current density of 10 mA cm −2 in a neutral electrolyte.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 99%
“…The 400‐SWNT/Pt exhibited a low overpotential of 27 mV to achieve current densities of 10 mA cm −2 , which are similar to those of Pt/C. Other precious metal‐based catalysts have also been reported, Zhang et al developed a well‐dispersed atomic Ir incorporated Co‐based hydroxide nanosheets with 9.7 wt% Ir. This catalyst displayed highly efficient OER catalytic performance with overpotential 373 mV at the current density of 10 mA cm −2 in a neutral electrolyte.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 99%
“…To date, the IrO 2 and RuO 2 noble metal oxides are regarded as active catalysts for this reaction . Song and co‐workers synthesized single Ir atoms and Ir clusters on 2D Co(OH) 2 for enhancement of its OER activity . These atomic Ir species anchored on defect‐rich Co(OH) 2 nanosheets showed excellent OER performance with rapid catalytic kinetics.…”
Section: Electrochemical Applicationmentioning
confidence: 99%
“…[41] In addition, Das [43] Additionally,abinuclear Mn-based catalyst, [(terpy)(SO 4 )Mn IV (O) 2 Mn IV (O 4 S)(terpy)] (terpy:2 ,2':6',2''-terpyridine) can also be synthesized by using MnSO 4 and terpy as the precursors and potassium peroxomonosulfate as the oxidant. Some highly dispersed metal-supported WOCs can be synthesized through chemical reduction.…”
Section: Chemical Reductiona Nd Oxidationmentioning
confidence: 99%
“…[99] Kinetic studies showedt hat oxygen evolutionw as rapid if cerium(IV) ammonium nitratew as used as the oxidant, and DFT calculations demonstrated that the attack of water on M=Os pecies was ak ey step in OÀOb ond formation.B rudvig and co-workers used an electrochemical quartz crystal nanobalance (EQCN) to revealt he homo-o rh eterogeneousn ature of WOCs. [138] In 2018, an ew type of iridium-based catalyst, iridium-incorporated cobalt hydroxide (Ir-Co),w as synthesized by Zhang et al [41] In 1.0 m phosphate-buffered saline (PBS), Ir-Co-0.2 (the molar ratio of Ir/ Co was 0.2) showedalow potential( 373 mV at j = 10 mA cm À2 ). [137] Iridium-substitutedP OMs can also catalyze the water oxidation with as trong oxidant, such as [Ru(bipy) 3 ] 3 + .…”
Section: Iridium-based Wocsmentioning
confidence: 99%